2019
DOI: 10.3390/ijerph16193662
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease Status among Adults from South Africa—Prevalence and Effect of Smoking

Abstract: Periodontal diseases are among the six most prevalent non-communicable diseases (NCDs) worldwide, constituting a burden for oral and general health. There is a shortage of epidemiological data on periodontal diseases in Africa. The aim of the present cross-sectional study was to present the periodontal status and cotinine levels of a South African population of adults. This study included individuals living in the Belville South area. Bleeding on probing (BOP) and pocket depth were recorded for each tooth, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 26 publications
4
25
0
Order By: Relevance
“…These studies have been supported by evidence that has shown that the risk of periodontitis is increased threefold in diabetic individuals as compared with nondiabetic individuals (Mealey and Oates 2006) and that adults with an glycated hemoglobin (HbA1c) level >9% have a significantly higher prevalence of severe periodontitis than those without diabetes (Preshaw et al 2012). Our previous findings showed a high prevalence of diabetes and periodontitis in a South African population from the Western Cape, Cape Town (Erasmus et al 2012;Chikte et al 2019). Therefore, in this study, we aimed to investigate the composition of the oral microbiome across all glucose tolerance statuses and periodontal diseases in South African adults from Cape Town.…”
Section: Introductionmentioning
confidence: 67%
“…These studies have been supported by evidence that has shown that the risk of periodontitis is increased threefold in diabetic individuals as compared with nondiabetic individuals (Mealey and Oates 2006) and that adults with an glycated hemoglobin (HbA1c) level >9% have a significantly higher prevalence of severe periodontitis than those without diabetes (Preshaw et al 2012). Our previous findings showed a high prevalence of diabetes and periodontitis in a South African population from the Western Cape, Cape Town (Erasmus et al 2012;Chikte et al 2019). Therefore, in this study, we aimed to investigate the composition of the oral microbiome across all glucose tolerance statuses and periodontal diseases in South African adults from Cape Town.…”
Section: Introductionmentioning
confidence: 67%
“…Globally, PD affects about 20%–50% of the population [ 13 ]. Developing nations have higher prevalence of PD among adolescents than developed countries with proportions ranging from 35% to 70% [ 14 , 15 ]. Smoking/tobacco use, obesity, poor oral hygiene and nutrition have all been associated with an increased risk of PD [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…While there is no simple explanation for this finding, it can be speculated that having teeth affected by oral disease leads to discomfort in daily life or that the presence of a denture is seen to be far more pleasing than the presence of dental pain. Previous studies from our group show a high degree of unmet dental treatment needs in the studied population; as such, potential inflammation, loose teeth, pain, and general discomfort have probably influenced the OHRQoL in the studied population [ 30 , 33 ].…”
Section: Discussionmentioning
confidence: 99%